ESTIMATION OF BENTONITE DEPOSITS OF UKRAINE ON A BALL SCALE - ANDRIEIEVA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The using of geological index for economical evaluation bentonitic deposits is considered. As conclusion, the Cherkas’ke deposit is the most perspective object.